1987
DOI: 10.1051/rphysap:01987002208077500
|View full text |Cite
|
Sign up to set email alerts
|

X-ray reflectivity of a Langmuir monolayer on water

Abstract: Résumé. 2014 Nous avons mis au point une cuve de Langmuir qui permet l'utilisation de la technique de réflexion des rayons X. A l'aide de ce dispositif nous avons pour la première fois étudié le profil de densité d'une monocouche de Langmuir directement sur l'eau. Cette expérience ouvre de nouvelles perspectives en particulier, pour des mesures précises de la rugosité des films solides sur l'eau.Abstract. 2014 We built a special Langmuir through allowing the use of X-ray reflectivity. Using the device we stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…Similar binding has been shown for a range of divalent cations (Richardson & Roser 1987;Gordziel et al 1981). Recently, Xray reflectivity studies have shown that Pb11 ions bind to stearic acid films with the stoichiometry Pb(stearate)2 (Bosio et al 1987), and it is reasonable to propose that Ca binds in a similar manner. Because the pK of stearic acid in the presence of Ca is ca.…”
Section: Discussionsupporting
confidence: 66%
“…Similar binding has been shown for a range of divalent cations (Richardson & Roser 1987;Gordziel et al 1981). Recently, Xray reflectivity studies have shown that Pb11 ions bind to stearic acid films with the stoichiometry Pb(stearate)2 (Bosio et al 1987), and it is reasonable to propose that Ca binds in a similar manner. Because the pK of stearic acid in the presence of Ca is ca.…”
Section: Discussionsupporting
confidence: 66%
“…[18,19] Specular reflection provides information on the electron-density variation (scattering length density variation) perpendicular to the surface with ngström-level resolution. Due to the loss of the phase information in conventional X-ray reflectivity experiments, the data analysis is generally based on finding proper electrondensity functions, whose reflectivity properties retrospectively best match the observed reflectivity data.…”
mentioning
confidence: 99%
“…The profile of the film in which a trilayer is expected features more peaks than were observed for trilayers of X-shaped molecules. In fittings of the XRR profiles to the theoretical equations, 43,44 a vertical orientation of the molecules was assumed and the electron density profile consisting of more slabs of different density than in the case of the X-shaped molecules was taken into consideration. The A 3 /A 1 ratio equals 2.65, indicating partial interdigitation of the molecules between the layers.…”
Section: T-shaped Bolaamphiphilementioning
confidence: 99%